Analisis Model ServqualL Terhadap Kepuasan Pelanggan (Studi Kasus Bangka City Hotel Pangkalpinang) - Anggraeni Yunita (UNSIKA (Universitas Singaperbangsa Karawang), 2018)
The aim of this research is to analyze whether 5 (five) dimension which is SerQual Model consisting of Tangible, Realibility, Responsiveness, Assurance and Emphaty have an effect on customer satisfaction of case study conducted at Bangka City Hotel Pangkalpinang. This research uses quantitative approach with multiple regression analysis method. In this study the authors use convenience sampling technique in which the way sampling is done by taking anyone who happened to stay at Bangka City Hotel during the study period. Of the 100 respondents selected, only 95 questionnaires can be processed. The results obtained are partially Tangible, Realibility, Responsiveness, and Emphaty variables affect customer satisfaction, except Assurance variable has no effect on customer satisfaction. But simultaneously, all wariabel consisting of Tangible, Realibility, Responsiveness, Assurance and Emphaty affect customer satisfaction. Keywords: ServQual, Tangible, Realibility, Responsiveness, Assurance, Emphaty